Attitudes and Practices of Healthcare Professionals and Clinical Medical Students on Contraception: A Cross-Sectional Study in Cape Coast, Ghana - Agbeno, Evans Kofi; Osarfo, Joseph; Anane-Fenin, Betty; Achampong, Emmanuel Kusi; Neequaye, Naa Adei; Opoku, Douglas Aninng; Aliyu, Mohammed; Ken-Amoah, Sebastian; Ofori, Anthony Amanfo; Ashong, Joycelyn A. (International Journal of Reproductive Medicine, 2021)
Background. Healthcare providers play a major role in the implementation of family planning policies. In Ghana, there has been a conscious effort to improve the knowledge of preservice and practicing health professionals on family planning. However, there have been concerns about the appropriateness of the attitudes and practices of these health cadres and, hence, their propensity to become barriers to the uptake of contraception in the general population. This study is aimed at assessing the attitudes and practices of healthcare workers and clinical-year medical students in contraceptives use, advocacy, and service provision. Methods. A cross-sectional survey was conducted among health workers and clinical-year medical students from January 1 to June 30, 2018. Variables assessed included sexual activity status, previous and current contraceptive use, and satisfaction with contraceptive use among others. Data from 400 self-administered, structured questionnaires comprising close- and open-ended questions was entered in SPSS version 22 and analysed using same. The variables assessed were presented as means, frequencies, and percentages. Results. About 58% of the respondents were sexually active. Half of the participants (50.2%) had used a form of contraception before, with condoms and other barrier methods being the most preferred (67.7%). However, only 18% of respondents were on a form of contraceptive at the time of the survey. Four out of five (82.6%) of the users of these contraceptives were satisfied with their past use. A little over half of the participants had discussed contraception with their partners. Over four-fifths of participants thought family planning was beneficial and were willing to encourage others to use a method of family planning. Majority (63.7%) of the participants had had formal training in family planning, but only 72 (18%) were actively involved in the provision of family planning services. Conclusions. Although the attitudes of the health workers and trainees toward family planning were excellent generally, only a few were using a method of contraception at the time of the survey despite the fact that most of them were sexually active. There is a need to intensify communication on behaviour change towards contraception among health professionals and clinical-year medical students in order to strengthen their role as change agents in an effort to improve community uptake.